A corrosion-resistant conveyor belt covering rubber and its preparation process
By using corrosion-resistant conveyor belt covering rubber composed of materials such as fluoroelastomer and tetrapropylene fluoroelastomer, and combining high-performance components such as modified graphene and modified basalt fiber, the problem of insufficient performance of existing conveyor belt covering rubber is solved, and higher corrosion resistance, mechanical properties and aging resistance are achieved.
Patent Information
- Application Number
- CN202411959641.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The corrosion resistance, mechanical properties and aging resistance of existing conveyor belt cover glue are insufficient, making it difficult to use in complex industrial environments for a long time.
Corrosion-resistant conveyor belt covering glue consisting of fluoroelastomer, tetrapropylene fluoroelastomer, hydrophobic flame retardant, modified graphene, modified basalt fiber, etc., and its performance is improved through an optimized preparation process.
The corrosion resistance, mechanical properties and aging resistance of the cover glue are significantly improved, so that it can be used for a long time without damage in harsh environments, and has better flame retardant and water resistance.
Smart Images

Figure BDA0005216779430000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conveyor belt covering rubber, and in particular to a corrosion-resistant conveyor belt covering rubber and a preparation process thereof. Background Art
[0002] In the field of industrial production, conveyor belts are the core equipment for material transportation, and the performance of their covering rubber is directly related to the overall efficiency and safety of the conveyor belts. However, traditional conveyor belt covering rubber has exposed a series of challenges when facing the complex and changeable application environment of modern industry. The primary problem is that its corrosion resistance is insufficient and it is difficult to resist the erosion of corrosive media such as acids, alkalis, and salts, which shortens the service life of the conveyor belt and even causes safety hazards. In addition, the limitations of traditional covering rubber in mechanical properties, flame retardant properties, and aging resistance also limit its application potential in high temperature, flammable and long-term operating environments.
[0003] In order to solve the above problems, the existing technology has made many rounds of improvement attempts. On the one hand, by adding auxiliary materials such as flame retardants and plasticizers, and introducing high-performance fibers, the flame retardancy, mechanical properties and wear resistance of the conveyor belt covering rubber are improved. On the other hand, the preparation process is optimized, such as improving the mixing, vulcanization and other steps to improve the uniformity and stability of the material. However, these improvement measures are not perfect. Therefore, the preparation method of the conveyor belt covering rubber in the existing technology still needs to be further improved to meet the higher requirements of industrial production. Summary of the invention
[0004] Technical issues solved
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a corrosion-resistant conveyor belt covering rubber and a preparation process thereof, which can effectively solve the problem that the corrosion resistance and mechanical properties of the conveyor belt covering rubber prepared by the prior art are not perfect.
[0006] Technical Solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A corrosion-resistant conveyor belt covering rubber, the corrosion-resistant conveyor belt covering rubber is composed of the following components: fluororubber, tetrafluoroethylene rubber, hydrophobic flame retardant, modified graphene, modified basalt fiber, silicon dioxide, zinc oxide, stearic acid, trichloroethyl phosphate, triallyl isocyanurate, phenolic resin, antimony trioxide, sulfur and diisopropylbenzene peroxide;
[0009] The hydrophobic flame retardant is prepared with hydromagnesite powder, Tris hydrochloric acid, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea as main raw materials;
[0010] The modified graphene is prepared by using poplar leaves as raw materials and undergoing carbonization and modification treatment;
[0011] The modified basalt fiber is obtained by modifying the basalt fiber with a silane coupling agent.
[0012] Furthermore, the preparation steps of the hydrophobic flame retardant are:
[0013] Step 1, weighing 10g of hydromagnesite powder and 200mL of deionized water, mixing and ultrasonically treating, then adding 0.7g of Tris hydrochloric acid under vigorous stirring and using sodium hydroxide solution to adjust the pH value to 8.5, adding 1g of dopamine hydrochloride and stirring at room temperature for 24h, vacuum filtering to remove the filtrate and washing with deionized water for 3 times, drying and grinding through a 200-mesh sieve, and the obtained product is recorded as a pretreatment component;
[0014] Step 2, weigh 8.5g of magnesium nitrate hexahydrate, 5.5g of aluminum nitrate nonahydrate and 200mL of deionized water, mix them, add 10g of the pretreatment component and disperse them evenly, the result is recorded as the first component, weigh 5.3g of urea, 2.5g of sodium dodecylbenzene sulfonate and 20mL of deionized water, mix them, stir until completely dissolved, and the result is recorded as the second component;
[0015] Step 3, drop the second component into the first component and adjust the pH value to 10 with sodium hydroxide solution, react at a constant temperature for 2 hours in a water bath at 80°C, remove the filtrate by vacuum filtration, wash with deionized water 3 times, dry and grind through a 200-mesh sieve to obtain a hydrophobic flame retardant.
[0016] Furthermore, the specific operation of the ultrasonic treatment in step 1 is ultrasonic dispersion at a frequency of 30 kHz for 30 minutes, the stirring speed of the vigorous stirring condition in step 1 is 800 r / min, the concentration of the sodium hydroxide solution in step 1 is 1 mol / L, and the specific operation of the drying treatment in step 1 is drying in an oven at 60° C. for 48 hours.
[0017] Furthermore, the specific operation of uniform dispersion in step 2 is stirring at a stirring speed of 500 r / min for 10 min, the specific operation of stirring until complete dissolution in step 2 is stirring at a stirring speed of 300 r / min for 20 min, the dripping rate in step 3 is 1 drop / s, and the specific operation of drying in step 3 is drying in an oven at 60°C for 12 h.
[0018] Furthermore, the preparation steps of the modified graphene are:
[0019] Step A, grinding the dried poplar leaves into powder and pouring them into a tube furnace, heating them to 800°C for carbonization for 1 hour in a nitrogen atmosphere, then activating them for 2 hours in a water vapor atmosphere, and then soaking them in concentrated sulfuric acid solution and potassium permanganate for 10 minutes in sequence, and the obtained powder components are recorded;
[0020] Step B: Pour the powder component into deionized water with a mass 10 times that of the powder component, add silane coupling agent KH-550 with a mass of 1% of the powder component after ultrasonic treatment, stir at a stirring speed of 300 r / min for 1 hour, and then dry it. After grinding through a 200-mesh sieve, the obtained modified graphene is obtained.
[0021] Furthermore, the heating rate in step A is 5°C / min, the specific operation of ultrasonic treatment in step B is ultrasonic dispersion at a frequency of 28kHz for 30min, and the specific operation of drying treatment in step B is drying in an oven at 68°C to constant weight.
[0022] Furthermore, the preparation method of the modified basalt fiber is:
[0023] 3g of silane coupling agent KH-570 was added to a 50% ethanol aqueous solution, stirred at a stirring speed of 300r / min for 10min, and then 10g of cleaned basalt fiber was added. After ultrasonic mixing for 5h, the filtrate was filtered to remove the filtrate and washed with deionized water for 3 times. After filtering out the filtrate, it was placed in an oven at 60°C and dried for 12h to obtain the modified basalt fiber.
[0024] Furthermore, the specific method of the cleaning treatment is to place the basalt fiber in acetone and perform ultrasonic cleaning at a power of 300 W for 3 hours, filter out the filtrate, and then place it in an oven at 65° C. to dry for 6 hours.
[0025] A preparation process of a corrosion-resistant conveyor belt covering rubber, the specific method of the preparation process is:
[0026] Weigh 30-40 parts by weight of fluororubber and 50-60 parts by weight of tetrafluoroethylene rubber, pour them into an open mill and plasticize them into master rubber respectively, add 3-5 parts by weight of hydrophobic flame retardant, 4-5 parts by weight of modified graphene, 10-12 parts by weight of silicon dioxide, 4-5 parts by weight of zinc oxide, 4-5 parts by weight of stearic acid, 6-8 parts by weight of trichloroethyl phosphate, 1-2 parts by weight of triallyl isocyanurate, 5-6 parts by weight of phenolic resin and 2-3 parts by weight of antimony trioxide after blending, continue to mix for 10 minutes, then add 6-8 parts by weight of modified basalt fiber and mix for 2 minutes, finally add 1-2 parts by weight of sulfur and 1-2 parts by weight of diisopropylbenzene peroxide and mix for 10 minutes, then adjust the roller distance to 5 mm thick and pass 8 times, then adjust the roller distance to 0.5 mm thick and pass 10 times, let it stand for 12 hours after unloading, and then vulcanize it to obtain the corrosion-resistant conveyor belt covering rubber.
[0027] Furthermore, the specific method of the vulcanization treatment is: placing it on a flat vulcanizer and vulcanizing it at a temperature of 170° C. for 16 minutes, and then vulcanizing it at a temperature of 150° C. for 6 hours.
[0028] Beneficial Effects
[0029] The present invention provides a corrosion-resistant conveyor belt covering rubber and a preparation process thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The fluororubber and tetrafluoroethylene rubber added in the present invention are both elastomers with excellent corrosion resistance and strong resistance to a variety of corrosive media. The combination of the two can further improve the corrosion resistance of the covering rubber, so that it can be used for a long time in harsh environments without being damaged. Moreover, both fluororubber and tetrafluoroethylene rubber have high heat resistance and can maintain stable physical and chemical properties at high temperatures, which enables the covering rubber to maintain good use effects in high temperature environments; secondly, the hydrophobic flame retardant added in the present invention can effectively block the combustion chain, reduce the combustion speed, and even extinguish the flame during the combustion process through its unique structure. Its hydrophobic property enables the covering rubber to maintain a certain flame retardant property in a humid environment. The introduction of the hydrophobic flame retardant makes the covering rubber have better water resistance, can maintain stable physical and chemical properties in a humid environment, and extend the service life.
[0031] 2. As a high-performance nanomaterial, graphene has excellent mechanical and electrical properties. By modifying it and introducing it into the covering rubber, the tensile strength, tear strength and wear resistance of the covering rubber can be significantly improved. Moreover, graphene has excellent thermal conductivity and can accelerate the heat transfer inside the covering rubber, so that it can still maintain good thermal stability in high temperature environments. Basalt fiber has high strength and modulus. By modifying it, its compatibility and interfacial bonding force with the covering rubber can be further improved, thereby enhancing the tear resistance of the covering rubber. Furthermore, basalt fiber itself has good aging resistance. Introducing it into the covering rubber can extend its service life and reduce the replacement frequency.
[0032] 3. The silicon dioxide, zinc oxide and stearic acid added in the present invention are used as common rubber compounding agents, which can significantly improve the processing performance and physical properties of the covering rubber, such as improving dispersibility, reducing viscosity and enhancing wear resistance; trichloroethyl phosphate and triallyl isocyanurate are used as cross-linking agents and plasticizers, which can optimize the cross-linked network structure of the covering rubber and improve its heat resistance and aging resistance; phenolic resin and antimony trioxide are used as flame retardants, which can further improve the flame retardant properties of the covering rubber and make it have a certain self-extinguishing property in fire.
[0033] 4. The corrosion-resistant conveyor belt covering rubber prepared by the present invention has significant innovations and advantages in terms of material components, preparation process and comprehensive performance. By introducing a variety of high-performance components and optimizing the preparation process, the corrosion resistance, mechanical properties, flame retardant properties and aging resistance of the covering rubber can be significantly improved, making it have broad application prospects and huge market potential. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The present invention will be further described below in conjunction with the embodiments.
[0036] The sources of some components in the embodiments and comparative examples are as follows:
[0037] Fluororubber, model FKM-246, Shanghai Sanaifu New Materials Co., Ltd.;
[0038] Tetrafluoroethylene rubber, EPDM, Northwest Rubber Research Institute;
[0039] Hydromagnesite powder, 99%, average particle size 3 μm, Dalian Yipu Co., Ltd.;
[0040] Tris hydrochloric acid, analytical grade, Tianjin Guangfu Fine Chemical Research Institute;
[0041] Dopamine hydrochloride, technical grade, Aladdin Co., Ltd.;
[0042] Magnesium nitrate hexahydrate, industrial grade, Tianjin Guangfu Fine Chemical Research Institute;
[0043] Aluminum nitrate nonahydrate, industrial grade, Tianjin Yongsheng Fine Chemical Co., Ltd.;
[0044] Urea, industrial grade, Beijing Chemical Plant;
[0045] Sodium dodecylbenzene sulfonate, industrial grade, Shandong West Asia Chemical Co., Ltd.;
[0046] Silane coupling agent KH-550, analytical grade, produced by Nanjing Daoning Chemical Co., Ltd.;
[0047] Silane coupling agent KH-570, analytical grade, Beijing Inokai Co., Ltd.;
[0048] Silicon dioxide, zinc oxide, stearic acid, trichloroethyl phosphate, triallyl isocyanurate, phenolic resin, antimony trioxide, sulfur and dicumyl peroxide, industrial grade, Shanghai Mairui Co., Ltd.
[0049] Example 1
[0050] A corrosion-resistant conveyor belt covering rubber of the present embodiment, the corrosion-resistant conveyor belt covering rubber is composed of the following components: fluororubber, tetrafluoroethylene rubber, hydrophobic flame retardant, modified graphene, modified basalt fiber, silicon dioxide, zinc oxide, stearic acid, trichloroethyl phosphate, triallyl isocyanurate, phenolic resin, antimony trioxide, sulfur and diisopropylbenzene peroxide;
[0051] The hydrophobic flame retardant is prepared with hydromagnesite powder, Tris hydrochloric acid, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea as main raw materials, and the preparation steps are as follows:
[0052] Step 1, weighing 10g of hydromagnesite powder and 200mL of deionized water, mixing them and ultrasonically dispersing them at a frequency of 30kHz for 30min, then adding 0.7g of Tris hydrochloric acid under vigorous stirring conditions at a stirring speed of 800r / min and using a sodium hydroxide solution with a concentration of 1mol / L to adjust the pH value to 8.5, adding 1g of dopamine hydrochloride and stirring the reaction at room temperature for 24h, vacuum filtering to remove the filtrate and washing with deionized water 3 times, placing it in an oven at 60°C and drying it for 48h, and then grinding it through a 200-mesh sieve, and the obtained result is recorded as a pretreatment component;
[0053] Step 2, weigh 8.5g of magnesium nitrate hexahydrate, 5.5g of aluminum nitrate nonahydrate and 200mL of deionized water, mix them, add 10g of the pretreatment component and stir at a stirring speed of 500r / min for 10min, the result is recorded as the first component, weigh 5.3g of urea, 2.5g of sodium dodecylbenzene sulfonate and 20mL of deionized water, mix them, stir at a stirring speed of 300r / min for 20min, the result is recorded as the second component;
[0054] Step 3, drip the second component into the first component at a dripping rate of 1 drop / s and adjust the pH value to 10 with sodium hydroxide solution, react at a constant temperature for 2 hours in a water bath at 80°C, remove the filtrate by vacuum filtration, wash with deionized water 3 times, dry in an oven at 60°C for 12 hours, and then grind through a 200-mesh sieve to obtain a hydrophobic flame retardant.
[0055] Modified graphene is prepared by carbonizing and modifying poplar leaves as raw materials, and the preparation steps are as follows:
[0056] Step A, grinding the dried poplar leaves into powder and pouring them into a tube furnace, heating them to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere for carbonization for 1 hour, then activating them in a water vapor atmosphere for 2 hours, and then soaking them in concentrated sulfuric acid solution and potassium permanganate for 10 minutes in sequence, and the obtained powder components are recorded;
[0057] Step B: Pour the powder component into deionized water with a mass 10 times that of the powder component, ultrasonically disperse it at a frequency of 28 kHz for 30 minutes, add silane coupling agent KH-550 with a mass of 1% of the powder component, stir it at a stirring speed of 300 r / min for 1 hour, place it in an oven at 68°C and dry it to constant weight, and grind it through a 200 mesh sieve to obtain the modified graphene.
[0058] Modified basalt fiber is prepared by modifying basalt fiber with a silane coupling agent, and the preparation method is as follows:
[0059] 3g of silane coupling agent KH-570 was added to a 50% ethanol aqueous solution, stirred at a stirring speed of 300r / min for 10min, and then 10g of cleaned basalt fiber was added. After ultrasonic mixing for 5h, the filtrate was filtered to remove the filtrate and washed with deionized water for 3 times. After filtering to remove the filtrate, it was placed in an oven at 60°C and dried for 12h to obtain modified basalt fiber. The specific method of cleaning treatment was to place the basalt fiber in acetone and ultrasonically clean it at a power of 300W for 3h, filter to remove the filtrate, and then dry it in an oven at 65°C for 6h.
[0060] A preparation process of a corrosion-resistant conveyor belt covering rubber, the specific method of the preparation process is:
[0061] Weigh 30 parts by weight of fluororubber and 50 parts by weight of tetrapropylene fluororubber, pour them into an open mill and plasticize them into master rubber respectively. After blending, add 3 parts by weight of hydrophobic flame retardant, 4 parts by weight of modified graphene, 10 parts by weight of silica, 4 parts by weight of zinc oxide, 4 parts by weight of stearic acid, 6 parts by weight of trichloroethyl phosphate, 1 part by weight of triallyl isocyanurate, 5 parts by weight of phenolic resin and 2 parts by weight of antimony trioxide and continue to mix for 10 minutes, then add 6 parts by weight of modified basalt fiber and mix for 2 minutes, finally add 1 part by weight of sulfur and 1 part by weight of diisopropylbenzene peroxide and mix for 10 minutes, then adjust the roller distance to 5 mm thick and pass 8 times, then adjust the roller distance to 0.5 mm thick and pass 10 times, let it stand for 12 hours after unloading, and then vulcanize it to obtain the corrosion-resistant conveyor belt covering rubber.
[0062] The specific method of the vulcanization treatment is: vulcanize on a flat vulcanizer at a temperature of 170° C. for 16 minutes, and then vulcanize at a temperature of 150° C. for 6 hours.
[0063] Example 2
[0064] A corrosion-resistant conveyor belt covering rubber of the present embodiment, the corrosion-resistant conveyor belt covering rubber is composed of the following components: fluororubber, tetrafluoroethylene rubber, hydrophobic flame retardant, modified graphene, modified basalt fiber, silicon dioxide, zinc oxide, stearic acid, trichloroethyl phosphate, triallyl isocyanurate, phenolic resin, antimony trioxide, sulfur and diisopropylbenzene peroxide;
[0065] The hydrophobic flame retardant is prepared with hydromagnesite powder, Tris hydrochloric acid, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea as main raw materials, and the preparation steps are as follows:
[0066] Step 1, weighing 10g of hydromagnesite powder and 200mL of deionized water, mixing them and ultrasonically dispersing them at a frequency of 30kHz for 30min, then adding 0.7g of Tris hydrochloric acid under vigorous stirring conditions at a stirring speed of 800r / min and using a sodium hydroxide solution with a concentration of 1mol / L to adjust the pH value to 8.5, adding 1g of dopamine hydrochloride and stirring the reaction at room temperature for 24h, vacuum filtering to remove the filtrate and washing with deionized water 3 times, placing it in an oven at 60°C and drying it for 48h, and then grinding it through a 200-mesh sieve, and the obtained result is recorded as a pretreatment component;
[0067] Step 2, weigh 8.5g of magnesium nitrate hexahydrate, 5.5g of aluminum nitrate nonahydrate and 200mL of deionized water, mix them, add 10g of the pretreatment component and stir at a stirring speed of 500r / min for 10min, the result is recorded as the first component, weigh 5.3g of urea, 2.5g of sodium dodecylbenzene sulfonate and 20mL of deionized water, mix them, stir at a stirring speed of 300r / min for 20min, the result is recorded as the second component;
[0068] Step 3, drip the second component into the first component at a dripping rate of 1 drop / s and adjust the pH value to 10 with sodium hydroxide solution, react at a constant temperature for 2 hours in a water bath at 80°C, remove the filtrate by vacuum filtration, wash with deionized water 3 times, dry in an oven at 60°C for 12 hours, and then grind through a 200-mesh sieve to obtain a hydrophobic flame retardant.
[0069] Modified graphene is prepared by carbonizing and modifying poplar leaves as raw materials, and the preparation steps are as follows:
[0070] Step A, grinding the dried poplar leaves into powder and pouring them into a tube furnace, heating them to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere for carbonization for 1 hour, then activating them in a water vapor atmosphere for 2 hours, and then soaking them in concentrated sulfuric acid solution and potassium permanganate for 10 minutes in sequence, and the obtained powder components are recorded;
[0071] Step B: Pour the powder component into deionized water with a mass 10 times that of the powder component, ultrasonically disperse it at a frequency of 28 kHz for 30 minutes, add silane coupling agent KH-550 with a mass of 1% of the powder component, stir it at a stirring speed of 300 r / min for 1 hour, place it in an oven at 68°C and dry it to constant weight, and grind it through a 200 mesh sieve to obtain the modified graphene.
[0072] Modified basalt fiber is prepared by modifying basalt fiber with a silane coupling agent, and the preparation method is as follows:
[0073] 3g of silane coupling agent KH-570 was added to a 50% ethanol aqueous solution, stirred at a stirring speed of 300r / min for 10min, and then 10g of cleaned basalt fiber was added. After ultrasonic mixing for 5h, the filtrate was filtered to remove the filtrate and washed with deionized water for 3 times. After filtering to remove the filtrate, it was placed in an oven at 60°C and dried for 12h to obtain modified basalt fiber. The specific method of cleaning treatment was to place the basalt fiber in acetone and ultrasonically clean it at a power of 300W for 3h, filter to remove the filtrate, and then dry it in an oven at 65°C for 6h.
[0074] A preparation process of a corrosion-resistant conveyor belt covering rubber, the specific method of the preparation process is:
[0075] Weigh 40 parts by weight of fluororubber and 60 parts by weight of tetrapropylene fluororubber, pour them into an open mill and plasticize them into master rubber respectively. After blending, add 5 parts by weight of hydrophobic flame retardant, 5 parts by weight of modified graphene, 12 parts by weight of silica, 5 parts by weight of zinc oxide, 5 parts by weight of stearic acid, 8 parts by weight of trichloroethyl phosphate, 2 parts by weight of triallyl isocyanurate, 6 parts by weight of phenolic resin and 3 parts by weight of antimony trioxide and continue to mix for 10 minutes, then add 8 parts by weight of modified basalt fiber and mix for 2 minutes, finally add 2 parts by weight of sulfur and 2 parts by weight of diisopropylbenzene peroxide and mix for 10 minutes, then adjust the roller distance to 5 mm thick and pass 8 times, then adjust the roller distance to 0.5 mm thick and pass 10 times, let it stand for 12 hours after unloading, and then vulcanize it to obtain the corrosion-resistant conveyor belt covering rubber.
[0076] The specific method of the vulcanization treatment is: vulcanize on a flat vulcanizer at a temperature of 170° C. for 16 minutes, and then vulcanize at a temperature of 150° C. for 6 hours.
[0077] Example 3
[0078] A corrosion-resistant conveyor belt covering rubber of the present embodiment, the corrosion-resistant conveyor belt covering rubber is composed of the following components: fluororubber, tetrafluoroethylene rubber, hydrophobic flame retardant, modified graphene, modified basalt fiber, silicon dioxide, zinc oxide, stearic acid, trichloroethyl phosphate, triallyl isocyanurate, phenolic resin, antimony trioxide, sulfur and diisopropylbenzene peroxide;
[0079] The hydrophobic flame retardant is prepared with hydromagnesite powder, Tris hydrochloric acid, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea as main raw materials, and the preparation steps are as follows:
[0080] Step 1, weighing 10g of hydromagnesite powder and 200mL of deionized water, mixing them and ultrasonically dispersing them at a frequency of 30kHz for 30min, then adding 0.7g of Tris hydrochloric acid under vigorous stirring conditions at a stirring speed of 800r / min and using a sodium hydroxide solution with a concentration of 1mol / L to adjust the pH value to 8.5, adding 1g of dopamine hydrochloride and stirring the reaction at room temperature for 24h, vacuum filtering to remove the filtrate and washing with deionized water 3 times, placing it in an oven at 60°C and drying it for 48h, and then grinding it through a 200-mesh sieve, and the obtained result is recorded as a pretreatment component;
[0081] Step 2, weigh 8.5g of magnesium nitrate hexahydrate, 5.5g of aluminum nitrate nonahydrate and 200mL of deionized water, mix them, add 10g of the pretreatment component and stir at a stirring speed of 500r / min for 10min, the result is recorded as the first component, weigh 5.3g of urea, 2.5g of sodium dodecylbenzene sulfonate and 20mL of deionized water, mix them, stir at a stirring speed of 300r / min for 20min, the result is recorded as the second component;
[0082] Step 3, drip the second component into the first component at a dripping rate of 1 drop / s and adjust the pH value to 10 with sodium hydroxide solution, react at a constant temperature for 2 hours in a water bath at 80°C, remove the filtrate by vacuum filtration, wash with deionized water 3 times, dry in an oven at 60°C for 12 hours, and then grind through a 200-mesh sieve to obtain a hydrophobic flame retardant.
[0083] Modified graphene is prepared by carbonizing and modifying poplar leaves as raw materials, and the preparation steps are as follows:
[0084] Step A, grinding the dried poplar leaves into powder and pouring them into a tube furnace, heating them to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere for carbonization for 1 hour, then activating them in a water vapor atmosphere for 2 hours, and then soaking them in concentrated sulfuric acid solution and potassium permanganate for 10 minutes in sequence, and the obtained powder components are recorded;
[0085] Step B: Pour the powder component into deionized water with a mass 10 times that of the powder component, ultrasonically disperse it at a frequency of 28 kHz for 30 minutes, add silane coupling agent KH-550 with a mass of 1% of the powder component, stir it at a stirring speed of 300 r / min for 1 hour, place it in an oven at 68°C and dry it to constant weight, and grind it through a 200 mesh sieve to obtain the modified graphene.
[0086] Modified basalt fiber is prepared by modifying basalt fiber with a silane coupling agent, and the preparation method is as follows:
[0087] 3g of silane coupling agent KH-570 was added to a 50% ethanol aqueous solution, stirred at a stirring speed of 300r / min for 10min, and then 10g of cleaned basalt fiber was added. After ultrasonic mixing for 5h, the filtrate was filtered to remove the filtrate and washed with deionized water for 3 times. After filtering to remove the filtrate, it was placed in an oven at 60°C and dried for 12h to obtain modified basalt fiber. The specific method of cleaning treatment was to place the basalt fiber in acetone and ultrasonically clean it at a power of 300W for 3h, filter to remove the filtrate, and then dry it in an oven at 65°C for 6h.
[0088] A preparation process of a corrosion-resistant conveyor belt covering rubber, the specific method of the preparation process is:
[0089] Weigh 35 parts by weight of fluororubber and 55 parts by weight of tetrapropylene fluororubber, pour them into an open mill and plasticize them into master rubber respectively. After blending, add 4 parts by weight of hydrophobic flame retardant, 5 parts by weight of modified graphene, 11 parts by weight of silica, 5 parts by weight of zinc oxide, 4 parts by weight of stearic acid, 7 parts by weight of trichloroethyl phosphate, 2 parts by weight of triallyl isocyanurate, 6 parts by weight of phenolic resin and 2 parts by weight of antimony trioxide and continue to mix for 10 minutes, then add 7 parts by weight of modified basalt fiber and mix for 2 minutes, finally add 2 parts by weight of sulfur and 2 parts by weight of diisopropylbenzene peroxide and mix for 10 minutes, then adjust the roller distance to 5 mm thick and pass 8 times, then adjust the roller distance to 0.5 mm thick and pass 10 times, let it stand for 12 hours after unloading, and then vulcanize it to obtain the corrosion-resistant conveyor belt covering rubber.
[0090] The specific method of the vulcanization treatment is: vulcanize on a flat vulcanizer at a temperature of 170° C. for 16 minutes, and then vulcanize at a temperature of 150° C. for 6 hours.
[0091] Comparative Example 1
[0092] The corrosion-resistant conveyor belt covering rubber and its preparation process provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the hydrophobic flame retardant in Example 1 is replaced with the flame retardant magnesium hydroxide.
[0093] Comparative Example 2
[0094] The corrosion-resistant conveyor belt covering rubber and its preparation process provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified graphene in Example 1 is replaced with graphene powder.
[0095] Comparative Example 3
[0096] The corrosion-resistant conveyor belt covering rubber and its preparation process provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the modified basalt fiber in Example 1 is replaced with unmodified basalt fiber.
[0097] Performance Testing
[0098] The corrosion-resistant conveyor belt covering rubbers prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested, and the obtained data is recorded in the following table;
[0099]
[0100] It can be seen from the data in the above table that the corrosion-resistant conveyor belt covering rubber in Examples 1-3 has better mechanical properties and better acid and alkali corrosion resistance than that in Comparative Examples 1-3, indicating that the corrosion-resistant conveyor belt covering rubber prepared by the present invention has excellent market application prospects.
[0101] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0102] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A corrosion-resistant conveyor belt covering rubber, characterized in that: The corrosion-resistant conveyor belt covering rubber is composed of the following components: fluororubber, tetrafluoroethylene rubber, hydrophobic flame retardant, modified graphene, modified basalt fiber, silicon dioxide, zinc oxide, stearic acid, trichloroethyl phosphate, triallyl isocyanurate, phenolic resin, antimony trioxide, sulfur and diisopropylbenzene peroxide; The hydrophobic flame retardant is prepared with hydromagnesite powder, Tris hydrochloric acid, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea as main raw materials; The modified graphene is prepared by using poplar leaves as raw materials and undergoing carbonization and modification treatment; The modified basalt fiber is obtained by modifying the basalt fiber with a silane coupling agent.
2. The corrosion-resistant conveyor belt covering rubber according to claim 1, characterized in that: The preparation steps of the hydrophobic flame retardant are: Step 1, weighing 10g of hydromagnesite powder and 200mL of deionized water, mixing and ultrasonically treating, then adding 0.7g of Tris hydrochloric acid under vigorous stirring and using sodium hydroxide solution to adjust the pH value to 8.5, adding 1g of dopamine hydrochloride and stirring at room temperature for 24h, vacuum filtering to remove the filtrate and washing with deionized water for 3 times, drying and grinding through a 200-mesh sieve, and the obtained product is recorded as a pretreatment component; Step 2, weigh 8.5g of magnesium nitrate hexahydrate, 5.5g of aluminum nitrate nonahydrate and 200mL of deionized water, mix them, add 10g of the pretreatment component and disperse them evenly, the result is recorded as the first component, weigh 5.3g of urea, 2.5g of sodium dodecylbenzene sulfonate and 20mL of deionized water, mix them, stir until completely dissolved, and the result is recorded as the second component; Step 3, drop the second component into the first component and adjust the pH value to 10 with sodium hydroxide solution, react at a constant temperature for 2 hours in a water bath at 80°C, remove the filtrate by vacuum filtration, wash with deionized water 3 times, dry and grind through a 200-mesh sieve to obtain a hydrophobic flame retardant.
3. The corrosion-resistant conveyor belt covering rubber according to claim 2, characterized in that: The specific operation of the ultrasonic treatment in step 1 is ultrasonic dispersion at a frequency of 30 kHz for 30 minutes, the stirring speed of the vigorous stirring condition in step 1 is 800 r / min, the concentration of the sodium hydroxide solution in step 1 is 1 mol / L, and the specific operation of the drying treatment in step 1 is drying in an oven at 60° C. for 48 hours.
4. The corrosion-resistant conveyor belt covering rubber according to claim 2, characterized in that: The specific operation of uniform dispersion in step 2 is stirring at a stirring speed of 500r / min for 10min, the specific operation of stirring until complete dissolution in step 2 is stirring at a stirring speed of 300r / min for 20min, the dripping rate in step 3 is 1 drop / s, and the specific operation of drying in step 3 is drying in an oven at 60°C for 12h.
5. The corrosion-resistant conveyor belt covering rubber according to claim 1, characterized in that: The preparation steps of the modified graphene are: Step A, grinding the dried poplar leaves into powder and pouring them into a tube furnace, heating them to 800°C for carbonization for 1 hour in a nitrogen atmosphere, then activating them for 2 hours in a water vapor atmosphere, and then soaking them in concentrated sulfuric acid solution and potassium permanganate for 10 minutes in sequence, and the obtained powder components are recorded; Step B: Pour the powder component into deionized water with a mass 10 times that of the powder component, add silane coupling agent KH-550 with a mass of 1% of the powder component after ultrasonic treatment, stir at a stirring speed of 300 r / min for 1 hour, and then dry it. After grinding through a 200-mesh sieve, the obtained modified graphene is obtained.
6. The corrosion-resistant conveyor belt covering rubber according to claim 5, characterized in that: The heating rate in step A is 5°C / min, the specific operation of ultrasonic treatment in step B is ultrasonic dispersion at a frequency of 28kHz for 30min, and the specific operation of drying treatment in step B is drying in an oven at 68°C to constant weight.
7. The corrosion-resistant conveyor belt covering rubber according to claim 1, characterized in that: The preparation method of the modified basalt fiber is: 3g of silane coupling agent KH-570 was added to a 50% ethanol aqueous solution, stirred at a stirring speed of 300r / min for 10min, and then 10g of cleaned basalt fiber was added. After ultrasonic mixing for 5h, the filtrate was filtered to remove the filtrate and washed with deionized water for 3 times. After filtering out the filtrate, it was placed in an oven at 60°C and dried for 12h to obtain the modified basalt fiber.
8. The corrosion-resistant conveyor belt covering rubber according to claim 7, characterized in that: The specific method of the cleaning treatment is to place the basalt fiber in acetone and perform ultrasonic cleaning at a power of 300 W for 3 hours, filter out the filtrate, and then place it in an oven at 65° C. and dry it for 6 hours.
9. A process for preparing a corrosion-resistant conveyor belt covering rubber according to any one of claims 1 to 8, characterized in that: The specific method of the preparation process is: Weigh 30-40 parts by weight of fluororubber and 50-60 parts by weight of tetrafluoroethylene rubber, pour them into an open mill and plasticize them into master rubber respectively, add 3-5 parts by weight of hydrophobic flame retardant, 4-5 parts by weight of modified graphene, 10-12 parts by weight of silicon dioxide, 4-5 parts by weight of zinc oxide, 4-5 parts by weight of stearic acid, 6-8 parts by weight of trichloroethyl phosphate, 1-2 parts by weight of triallyl isocyanurate, 5-6 parts by weight of phenolic resin and 2-3 parts by weight of antimony trioxide after blending, continue to mix for 10 minutes, then add 6-8 parts by weight of modified basalt fiber and mix for 2 minutes, finally add 1-2 parts by weight of sulfur and 1-2 parts by weight of diisopropylbenzene peroxide and mix for 10 minutes, then adjust the roller distance to 5 mm thick and pass 8 times, then adjust the roller distance to 0.5 mm thick and pass 10 times, let it stand for 12 hours after unloading, and then vulcanize it to obtain the corrosion-resistant conveyor belt covering rubber.
10. The process for preparing a corrosion-resistant conveyor belt covering rubber according to claim 9, characterized in that: The specific method of the vulcanization treatment is: placing on a flat vulcanizer at a temperature of 170° C. for 16 minutes, and then vulcanizing at a temperature of 150° C. for 6 hours.